Brexit and the UK constitution - Craig, P (Oxford University Press, 2019)
This chapter is, for obvious reasons, not a modification of the chapter from the previous edition. It is a completely new chapter, which considers the effect of Brexit on the UK constitution. There is discussion of the constitutional implications of triggering exit from the EU, and whether this could be done by the executive via the prerogative, or whether this was conditional on prior legislative approval through a statute. The discussion thereafter considers the constitutional implications of Brexit in terms of supremacy, rights, executive accountability to the legislature and devolution. The chapter concludes with discussion as to the paradox of sovereignty in the context of Brexit.